Jenis Dan Zat Gizi Pangan Jajanan Anak Sekolah Di Kantin Sekolah Dasar - Ayunda Firmani Wahyusa; Luh Suranadi; Irianto Irianto; AASP Chandradewi (Poltekkes Kemenkes Mataram, 2020)
Background : The eating patterns of school children tend to prefer school snacks rather than food at home. This habit occurs because children spend a quarter of their time in school. Contributions to the nutritional status of school children can be obtained through snacks both in terms of type and nutrient content. Objectives : Knowing the types and nutrients of snacks for school children in elementary school canteen. Methods : This research is a literature study which summarizes some relevant literature with research topics, namely the types and nutrients of snacks for elementary school children. Results : Types of snacks are the main food, snacks / drinks and drinks are available throughout the elementary canteen. Whereas fruit snacks are only available in 2 elementary canteens. Nutrient nutrients for daily intake exceeds the recommended interlude of> 20%. The price commonly used by students to buy snacks is Rp.2,725. Amount of student allowance> Rp. 5,000. Elementary school children mostly have normal nutritional status. Conclusion : The elementary school canteen has not yet fulfilled the requirements for types of snacks for school children. Nutrients for daily intake meet the recommendations. Prices commonly used by students to buy snacks are an average of Rp. 2,725 from allowance> Rp. 5,000. Elementary school children are mostly of normal nutritional status.